La mémoire du crime. Complaintes de tradition orale, justice et société dans la Bretagne d’Ancien Régime - Éva Guillorel (Criminocorpus)
Breton ballads collected from oral tradition are often neglected by early modern historians. However, they provide a rich source for studying violence and justice. Although they were recorded in the nineteenth century by antiquarians and folklorists, they have preserved the memory of local events that took place between the sixteenth and eighteenth centuries. Most of these ballads deal with murders, rapes and infanticides. The comparison between them and written documents such as judicial archives reveals two different and complementary discourses on early modern Brittany.